'If I had known the fertility health facts sooner…' Knowledge gaps as a barrier to effective fertility management: findings from the understanding fertility management in contemporary Australia survey. (4th July 2019) - Monester, Joshua; Fisher, Jane; Kirkman, Maggie; Rowe, Heather; Holton, Sara
Abstract: Background: Optimal fertility management enables women and men to avoid and achieve conception and parenthood when desired. A lack of knowledge about sexual, reproductive and fertility matters may impede a person's ability to manage their fertility effectively. Little is known about current gaps in fertility knowledge among Australians. Purpose: To identify information and knowledge gaps about fertility management among women and men of reproductive age living in Australia. Method: A sample of 18- to 50-year-old women and men ( N = 2235) randomly recruited from the Australian Electoral Roll in 2013. Respondents completed a self-administered, anonymous questionnaire that concluded with the option to provide free-text comments elaborating on their fertility management. These comments were analysed thematically to identify gaps in fertility management knowledge and information. Results: Of the 519 participants' comments, 472 were included in the analysis: 366 (77.5%) from women and 106 (22.5%) from men. Most comments related to contraception or fertility problems. Two themes about contraception were identified: (1) lack of information and knowledge about contraception and concerns about side-effects and (2) inadequate contraceptive education. Two themes about fertility problems were identified: (1) a lack of information and knowledge about fertility and (2) difficulties conceiving, including access to assisted reproductive treatments and other therapies. No major gender or age differences were identified across the themes. Conclusions: Many Australian women and men would welcome education and public health campaigns about contraceptive options and age-related fertility decline. Such interventions may enable women and men to manage their fertility and achieve their reproductive goals.